Representasi Propaganda dan Ideologi Perang dalam Anime Spy x Family melalui Analisis Semiotika Roland Barthes - Fita Yauma Sabita; Sarwo Edy; Ike Desi Florina (PERSPEKTIF, 2026)
This study analyzes the representation of propaganda and war ideology in the anime Spy x Family episodes 39–40. The research focuses on Loid Forger’s childhood, which reveals how war narratives, hostility toward the enemy, and militaristic values are constructed through media, family, social environment, and children’s play. This study employs a qualitative descriptive approach using Roland Barthes’ semiotic analysis, which includes denotation, connotation, and myth. Jacques Ellul’s propaganda theory is also used to classify the forms of propaganda represented in the selected scenes. The findings show that war propaganda is represented through integration, vertical, horizontal, sociological, and political propaganda. Sociological propaganda appears as the most dominant form because war ideology operates subtly through daily habits, social language, peer pressure, and children’s games. These findings indicate that Spy x Family functions not only as entertainment, but also as a medium of social criticism against the normalization of war, the dehumanization of enemies, and the formation of military identity from an early age. This study emphasizes the importance of critical media literacy in interpreting ideological messages embedded in popular culture